Etika Kepemimpinan dalam Membentuk Budaya Organisasi yang Berintegritas - Susan Febriantina; Jennah Marsha Sanjaya; Nadiva Azzahra; Thabita Salsabila; Vidya Indah Nurhafiza (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This study aims to analyse the relationship between ethical leadership, organisational culture, and employee performance in the context of modern organisations. Through a comprehensive literature review, this study reveals that ethical leadership and a positive organisational culture have a significant influence on employee performance. Ethical leadership, characterised by leaders' concrete actions in implementing moral values, creates a work environment that supports ethical and innovative behaviour. A strong organisational culture, which reflects the shared values and norms adopted by members of the organisation, also plays an important role in shaping employee behaviour and improving performance. In addition, employee engagement and employee commitment are important factors that mediate the relationship between ethical leadership, organisational culture and employee performance. The findings of this study conclude that investment in ethical leadership development and the establishment of a positive organisational culture are strategic steps for organisations to achieve superior and sustainable performance.